Building the personal reputation of collaborators in organizations (AACINI - International Journal of Industrial Engineering, 2023)
This article develops a conceptual model of the personal reputation of collaborators in organizations.. This article develops a conceptual model of the personal reputation of collaborators in organizations. This construct has gradually advanced under the single approach (unidimensional scale) study. However, the study of the predictor variables and their dimensions with the different types-dimensions of personal reputation in the literature is almost nonexistent. Therefore, it is identified that predictors such as perceived integrity, job performance, and political skill and their dimensions could be particularly associated with the types-dimensions of personal reputation such as task reputation, social reputation, and integrity reputation. This article thus aims to give continuity to the literature related to the assessment of predictors and personal reputation through the analysis of their dimensions and to promote the study of personal reputation by using the multidimensional scale proposed by Zinko, Gentry, and Laird. Finally, this manuscript states that this conceptual model requires analysis and empirical testing
Keywords: personal reputation; conceptual model; predictors; organizations